Penata Rias Pria yang Merias Wanita Perspektif Hadis; Kajian Hadis Tematik - Aulia Shabrina Rabbani; Muhid; Andris Nurita (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2023)
This article discusses the profession of a male makeup artist who makes women’s makeup. Islam instructs humans to work, but the work done must be based on Islamic Shari’ah. The implementation of the work of make-up artists carried out by men who make up women today has often been found. In fact, it is no longer a taboo to see men in this profession. In this case, the work done by men who do make-up for their female consumers, the make-up artist will directly touch, look at the face, see the private parts such as the hair and neck of the client directly. This research will present hadiths related to the profession of male make-up artists who make up women, where the search for hadith data uses the maudhu’i (thematic) method. This research includes a qualitative research model and includes a type of library research, so that the source of the data collected in the study is in accordance with the theme of the research discussion.